Numerical Investigation of High Pressure CO2-Diluted Combustion Using a Flamelet-based Approach. Issue 11 (1st November 2020) - Indelicato, Giuseppe; Lapenna, Pasquale Eduardo; Concetti, Riccardo; Caputo, Maddalena; Valorani, Mauro; Magnotti, Gaetano; Creta, Francesco
ABSTRACT: Direct-fired oxy-fuel combustion as a heat source is utilized in supercritical carbon dioxide (sCO2 ) power cycles, such as the Allam cycle, which has shown promise in delivering higher efficiencies while achieving the complete capture of combustion products in future generation carbon-neutral power plants. The design of dedicated burners for such cycles is key in determining their overall efficiency and viability. We present a series of numerical simulations on a prototype burner, currently in development, operating in an essentially non-premixed regime with a high pressure gaseous fuel, burning in the presence of a hot oxidant flow containing a mixture of recycled CO2 and pure oxygen. Simulations rely on a turbulent combustion model based on a simplified approach for diluted steady laminar flamelets. We investigate the effect of the degree of dilution as well as pressure on the flame structure, revealing a concurrent change in stoichiometric mixture fraction and quenching scalar dissipation. We also assess the effect of injector recess and of swirl in the oxidizer stream.